Conversational Storytelling: Classroom Teaching through Story Parallels Entrepreneurial Need for Engagement - Barbara A. Karanian; Mona Eskandari; Ville Taajamaa (United States, 2022)
Someone recently asked me, “What do you do in your class? I mean, I walk into
your classroom, sit down, then what happens?” Ok, I thought, I know how to answer this
question: I wanted to enthusiastically explain the structure of the class as a theoretical
blend of psychology, engineering design methods and art; discuss the intentional purpose
of building the curriculum iteratively and differently every term, based on the unique
developing social dynamics 13, 41 of every class.
Something stopped me and I resisted responding. In that moment, I remember
feeling the need to shift from an automatic theoretical response 48 to some other,
hopefully novel approach, that would underline how I teach; clarify what occurs in the
classroom. I thought I had the answer as an Instructor. And, as I struggled in my
response, to do what I teach, and avoid responding with a rehearsed, practiced pitch24 , I
realized that the response in my head to the question, “What happens in your class?” was
a conversation stopper. It was necessary to formulate a response that was a conversation
starter. Thus, I began sifting through the memorable moments in my mind, to find a short
story that would invite someone right into the classroom and step into the role of student;
a student required to act as both storyteller and audience. And, at the same time,
consider how the story might inform the early stage Professor preparing to teach for the
first time– a concept often parallel to the inspirational phase of an entrepreneurial
venture. One must figure out the passion and iteration on the product, the new creation,
and who the audience is.
Imagine the experience as a student in the class:
Jon walks into the classroom and sits down at the long seminar table. He quietly
suggests that while he is feeling confident about what he has done in his accomplishments
at school, coordinating early seed funding for his start-up, he is not feeling so good about
what is next for him.
During the first moments of class, Jon begins his story, “This is my last class. I
am fulfilling my final credits for the graduate program in Mechanical Engineering,” He
continues his story in a comfortable, conversational manner, and quietly leads with the
emotion behind his work, “We started this little company that makes and analyzes
affordable and reliable blood tests that will change the health and wellness for people in
remote areas of the world. For the first time in their lives, millions of people in third
world countries will receive the care they need and deserve.” The classroom was silent.
The non-verbal responses of the other students in class indicated variations of effective
engagement. Their bodies moved forward – some students are leaning towards him,
others adjust their bodies so they can get a better view, all are focused on Jon, all eyes
are riveted. When Jon stopped speaking, the room is still. There are different kinds of
silence; you feel it immediately – this is a silence of deep engagement.
The Instructor breaks the silence, “What are your impressions of Jon’s story?”
Classmates in graduate engineering, design, business, law, and humanities make it
clear to Jon that he is a natural “conversational storyteller.” One classmate explained,
“Everyone can’t do what you just did. You make it understandable and comfortable. And
it’s a meaningful, memorable story – it’s clear to us that you didn’t do the start-up just to
say you did it. ” They all left the classroom that day, planning to do the homework Jon
inspired: create pages of short stories from every part of your life. Be so comfortable
with the stories that they become second nature, a natural way to respond, and reliable
preparation for a conversation with a classmate, an advisor, a team mate on a project, an
interviewer for your dream job, a venture capitalist, a board of a non profit. They also
wondered what Jon meant when he suggested he was not confident about his future. We
will return to the story of Jon later in the Conversational Storytelling section of the paper.
2016 ASEE Annual Conference & Exposition